A taxonomic revision of the genus Scybalocanthon Martínez, 1948 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) - Silva, Fernando A. B.; Valois, Marcely (Zootaxa, 2019)
The genus Scybalocanthon Martínez, 1948 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) is revised and now consists of 23 valid species. Eight new species are described: S. acrianus new species, S. adisi new species, S. arnaudi new species, S. chamorroi new species, S. federicoescobari new species, S. haroldi new species, S. martinezi new species, and S. papaxibe new species. Scybalocanthon uniplagiatus (Schmidt, 1922) new combination is placed in the genus for the first time. The following species previously assigned to Scybalocanthon are here placed in the genus Canthon Hoffmannsegg, 1817: Canthon arcabuquensis (Molano & Medina, 2010) new combination, Canthon balachowskyi (Martínez & Halffter, 1972) new combination, Canthon luctuosus Harold, 1868, Canthon magnus (Molano & Parrales, 2015) new combination, and Canthon nigellus Schmidt, 1922. Scybalocanthon imitans (Harold, 1868) is a new junior subjective synonym of S. sexspilotus (Guérin-Méneville, 1855) and S. zischkai Martínez, 1949 is a new junior subjective synonym of S. aereus (Schmidt, 1922). Lectotypes are designated for S. aereus (Schmidt, 1922), S. cyanocephalus (Harold, 1868), S. darlingtoni (Paulian, 1939), S. kaestneri (Balthasar, 1939), S. maculatus (Schmidt, 1920), S. moniliatus (Bates, 1887), S. pinopterus (Kirsch, 1873), S. pygidialis (Schmidt, 1922), S. trimaculatus (Schmidt, 1922), and S. uniplagiatus (Schmidt, 1922). A neotype is designated for S. sexspilotus (Guérin-Méneville, 1855). A detailed literature review, synonymies, diagnosis, key for species identification, illustration of key morphological characters, as well as data of the studied material and geographic distribution are provided for each species.